Reducción del estrés salino en el crecimiento y algunas características fisiológicas de la haba (Vicia faba L.) mediante el remojo de las semillas con ácido salicílico (Journal of the College of Basic Education, 2022)
An experiment was carried out by using plastic pots during growing season 2014 – 2015 in private nursery in Baghdad governorate to study the effect of seeds soaking with Salicylic acid ( SA ) ( 0 , 0.5 , 1 ) mM and salt stress with NaCl ( 0 , 50 , 100 ) mM and their interaction in some growth parameters in Vicia faba L. included : plant height , branches number , pods number , pods length , pods weight , weight of 100 seeds , chlorophyll content , protein percentage and electrolyte leakage in leaf tissues . The experiment designed according to Completely Randomized Design ( CRD ) with three replications . Results showed that salinity stress significant reduction in the averages of growth parameters (plant height , branches number , pods number , pods length , pods weight , weight of 100 seeds , chlorophyll content , protein percentage ) and significant increased in electrolyte leakage , while the seeds soaking with SA caused a significant increase in all the growth parameters and significant reduction in electrolyte leakage . The results showed significant effect of interaction between both factors in all traits .